Electric ferry ecosystem for sustainable inter-island transport in the Philippines: a prospective simulation for Davao City – Samal Island Route - Eleonor V. Palconit; Michael Lochinvar S. Abundo (International Journal of Sustainable Energy, 2019)
The development of a prospective simulation will serve as a guide in converting a diesel engine into 100% electric engine, this conversion will solve the problems facing nowadays in an energy crisis and greenhouse gas emission. The simulation derives the estimated power engine, the battery pack to be installed and the photovoltaic wattage for charging while transporting passengers and goods from Davao City to Samal Island Philippines. The results give an estimated power engine of 24.07 kW, 7.1 kA- hour battery bank and 64 kW of the photovoltaic module to charge the battery while on voyage. This study further helps the boat owner to find the suitable engine requirement in converting into the electric ferry. The prospective simulation is the stepping-stone in moving towards green energy source and electric mobilisation in the maritime sector.